2009
DOI: 10.1111/j.1460-2695.2009.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

About cracks, dunce caps and a new way to stop cracks

Abstract: A B S T R A C T Recently, the 'method of tensile triangles' has been introduced for optimizing the shape of notches by adding material at overloaded regions but also to remove unloaded material from an oversized design proposal.In this work, we apply the method to demonstrate that the unloaded region in the vicinity of a crack has the shape of spindle-shaped hole, which looks like two dunce caps mirrored at the crack line. Also, these shapes can be predicted by the 'method of tensile triangles' without any FEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Mattheck et al [13,14] have developed and used the biological growth method, which reduces stress concentration using the fillet radius technique and biological growth method. Pranesh et al [15,16] also showed that stress concentration occurred at the corners of the lowpressure surface of the observation window and the notch regions of the flange.…”
Section: Introductionmentioning
confidence: 99%
“…Mattheck et al [13,14] have developed and used the biological growth method, which reduces stress concentration using the fillet radius technique and biological growth method. Pranesh et al [15,16] also showed that stress concentration occurred at the corners of the lowpressure surface of the observation window and the notch regions of the flange.…”
Section: Introductionmentioning
confidence: 99%